Entrepreneurship in an Alpine micro-nation: The case of Liechtenstein - Schuessler, F.; Schaper, Michael; Kraus, S. (Inderscience, 2014)
Although it is one of the smallest nation-states in existence, the Principality of Liechtenstein has one of the highest rates of entrepreneurship in the developed world. More than 14% of the population is self-employed or works in their own firm, and there are more than 4,000 businesses in a population of just 35,000 people, even though the country has few natural resources or advantages. This article examines how such a micro-nation has succeeded in spite of its disadvantages. The paper outlines the history of the principality and its economic development over the last century, identifies the main drivers for the very positive entrepreneurial climate in the Alpine micro-nation, and outlines current opportunities and problems faced by entrepreneurs in the country.